Behavioral changes of food allergic model mice during light and dark period - Yusuke Miyazaki; Koji Kobayashi; Takahisa Murata (Elsevier, 2023)
Although an animal model of food allergy has been used to investigate its progression mechanism, most researcher could not assess its symptoms for long especially under dark environment. We assessed the behavioral changes of food allergic mice using an image analysis system to track a mouse under both light and dark environments. Mice were sensitized with intraperitoneal ovalbumin (OVA) injections and challenged ten times with oral OVA administration. The OVA challenges induced weight loss and diarrhea. We assessed their behavior and found that the OVA challenges decreased their total moving distance during the dark period. We also revealed that the OVA challenges increased the inactive time of mice during the dark period. Interestingly, these changes were not observed or very small during the light period. We next assessed the location of mice in the home-cage and found that the OVA challenges increased the time when mice stayed at corners and decreased the time at the center during the dark period. These observations suggest mental abnormality of mice. Indeed, the OVA challenges increased the immobility time of mice in the tail suspension test. Thus, food allergic mice exhibited reduced activity and might exhibit psychological symptoms during dark period.